2021
DOI: 10.7150/thno.62046
|View full text |Cite
|
Sign up to set email alerts
|

Milk-derived extracellular vesicles alleviate ulcerative colitis by regulating the gut immunity and reshaping the gut microbiota

Abstract: Rationale: Bovine milk constitutes an essential part of human diet, especially for children, due to its enrichment of various nutrients. We recently developed an effective protocol for the isolation of extracellular vesicles from milk (mEVs) and discovered that mEVs contained large amounts of immune-active proteins and modulated the gut immunity and microbiota in healthy mice. Here, we aimed to explore the therapeutic effects of mEVs on inflammatory bowel disease. Methods: Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 59 publications
(71 reference statements)
5
114
1
Order By: Relevance
“…Teng et al showed that plant-derived EVs regulated gut microbiota composition and localization, and enhanced the gut barrier function to alleviate colitis [44]. It was documented in our previous research that milk-derived EVs could alleviate colitis via modulating gut microbiota [45]. Here, we found that LGG-EVs restored the disorders of αand β-diversity induced by DSS.…”
Section: Discussionsupporting
confidence: 58%
“…Teng et al showed that plant-derived EVs regulated gut microbiota composition and localization, and enhanced the gut barrier function to alleviate colitis [44]. It was documented in our previous research that milk-derived EVs could alleviate colitis via modulating gut microbiota [45]. Here, we found that LGG-EVs restored the disorders of αand β-diversity induced by DSS.…”
Section: Discussionsupporting
confidence: 58%
“…Mice were housed in an animal care facility and provided with sufficient food (Beijing Keao Xieli Feed Co., Ltd., Beijing, China) and water. Colitis was induced by 3.5% dextran sulfate sodium (DSS, Yeasen Biotech, Shanghai, CN) administration in the drinking water ( 23 ) and the mice were treated Q7-EVs by gavage ( 23 , 24 ). The mice were acclimated for a week and randomly divided into four groups: control group (PBS, daily), DSS+PBS group (PBS, daily), DSS+10 μg Q7-EVs group (0.5 mg/kg body weight Q7-EVs, daily), DSS+20 μg Q7-EVs group (1 mg/kg body weight Q7-EVs, daily).…”
Section: Methodsmentioning
confidence: 99%
“…These results were replicated in vivo in a mouse model of ulcerative colitis. Moreover, the administration of bovine milk exosomes improved wide aspects of cytokine homeostasis, immune response, and modestly improved gut microbiota profile [ 139 ]. Thus, bovine milk exosomes constitute a promising therapeutic tool in managing intestinal inflammatory disorders.…”
Section: Beneficial Effects Of Bovine Milk Exosomes On Overall Healthmentioning
confidence: 99%